School Assistance for Effective Facility Management to Support Quality and Child-Friendly Learning Processes - Rudolf Kempa; Arnold Sahalessy; Paul Arjanto; Vando Kristi Makaruku; Vicardy Kempa; Nedhy Tisan (DEVOTIONIS, 2024)
Effective management of school facilities and infrastructure is crucial for supporting the educational process. At SD Negeri Air Louw Ambon, significant challenges exist in optimizing the use and maintenance of existing facilities, primarily due to a lack of knowledge and skills among staff. This community service initiative aimed to provide assistance in improving facility management at the school, ultimately fostering a quality and child-friendly learning environment. The project involved stages of consultation and mentoring, workshops and training, and ongoing monitoring and evaluation. Results indicated substantial improvements in the knowledge and skills of teachers and staff, enhanced physical conditions of school facilities, a safer and more comfortable environment for students, and increased active participation from the entire school community. These improvements have significant implications for educational administration, supporting more effective leadership, strategic planning, and community engagement. The initiative underscores the importance of continuous professional development, regular maintenance, and stakeholder involvement in creating a sustainable and high-quality learning environment. Future efforts should focus on maintaining these gains and building on successful strategies to support long-term educational goals.